Antifouling Properties of Brown Macroalgae Dictyota dichotoma Collected from the Red Sea; Comparison of Surface and Whole Thallus Extracts - Salim Basndwah, Dina Saeed (Journal of King Abdulaziz University: Marine Sciences, 2022)
The metabolites produced by the marine macroalgae are considered as a source for the natural product antifoulants. In this study, the surface and whole thallus extracts of the marine macroalgae Dictyota dichotoma was tested against a biofilm-forming bacterial strain Vibrio harveyi and barnacle larval settlement to understand the best extraction strategies for antifouling screening bioassays. The surface extracts were prepared in different time duration by dipping the algal samples for 10, 20 and 30 seconds in hexane. The results indicated that the extracts (both surface and whole thallus) obtained from the macroalgal samples have strong antifouling activities against the bacterial strain V. harveyi and barnacle larvae settlement. The extraction duration of the surface extracts strongly affected the antifouling activity. In all the assays, the surface extract obtained by 30 sec. dipping in the solvent showed high inhibitory activity than whole thallus extract. In conclusion, this study indicated the necessity for the inclusion of surface extraction methods for antifouling screening assays using marine macroalgae as a source for natural products.